Answer:
Add the exponents and keep the same base Then find the reciprocal and change the sign of the exponent .
Explanation:
Given the expression (2^3)(2^- 4), we will apply the law of indices below to solve the equation;
![a^m * a^n = a^(m+n)\\a^(-m) =(1)/(a^m)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ksjio44irqp1c3k7fi6nqvblf5wd8br7l4.png)
Applying this on the given expression;
![(2 ^ 3)(2 ^(-4))](https://img.qammunity.org/2021/formulas/mathematics/high-school/zgpd8ylzkrftbsmu2b44oywoxl611kz4o0.png)
Step 1: Add the exponents and keep the same base as shown;
![= (2 ^ 3)(2 ^(-4))\\\\= 2^(3+(-4))\\\\ = 2^(3-4)\\\\= 2^(-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/qmkbzw2nj9mudykh9emotpklzvfwrc0qqt.png)
Step 2: Find the reciprocal and change the sign of the exponent
![= 2^(-1) \\= (1)/(2^1)\\= (1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/xzsdec723lrwxpk5utxddkfr7qox1j29hz.png)